Actividades motoras y la regulación de emociones en niños de la institución educativa inicial N° 767, San Pablo 2024 - Rodriguez Linares, Silvia (2025)
The objective of the present research study is to determine the level of relationship between the application of motor activities and the regulation of emotions in children of the Initial Educational Institution N°767 San Pablo 2024. The present study is framed within a quantitative and It is relational in nature. The research design adopted is non-experimental. The investigated population is made up of all the children a total of 63 infants. For data collection, the observation technique is used, using an observation guide as an instrument. This instrument was previously subjected to a validation and reliability process. Validity was evaluated by a panel of three experts in the area, and reliability was determined using Cronbach's Alpha coefficient. The Spearman's Rho test coefficient was 0.746, which indicates a strong positive correlation. between these two variables. The bilateral significance of 0.05 supports this relationship, it is concluded that the null hypothesis is rejected and the general hypothesis is accepted if there is a relationship between applications of motor activities with the regulation of emotions in children of the Institución Educativa Inicial N°767 San Pablo 2024.